2012
DOI: 10.1007/s10753-012-9443-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-27a* and miR-532-5p and Upregulation of miR-146a and miR-155 in LPS-induced RAW264.7 Macrophage Cells

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that are involved in the epigenetic regulation of cellular processes. To identify more miRNAs which are involved in the macrophage inflammatory response to lipopolysaccharide (LPS) stimulation and dissect the mechanisms more clearly, microRNA profiling of LPS-treated RAW264.7 macrophage cells was performed by initial high-throughput array-based screen and further real-time RT-PCR validation; bioinformatics approaches were used to analyze the target genes of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 22 publications
1
64
0
Order By: Relevance
“…miRNAs are involved in the regulation of diverse processes, including apoptosis, metabolism, cell fate determination, and host-pathogen interactions (9). miRNAs have been shown to regulate the host antiviral response by altering the expression of host genes required for virus replication and antiviral response (10)(11)(12) or by directly targeting viral genomes and/or transcripts (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…miRNAs are involved in the regulation of diverse processes, including apoptosis, metabolism, cell fate determination, and host-pathogen interactions (9). miRNAs have been shown to regulate the host antiviral response by altering the expression of host genes required for virus replication and antiviral response (10)(11)(12) or by directly targeting viral genomes and/or transcripts (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…**p50.01 and ***50.001 when compared with corresponding control samples. Cheng et al, 2012;Ruggiero et al, 2009;Tili et al, 2007;Zheng et al, 2012) and miR-125b (Androulidaki et al, 2009;El Gazzar & McCall, 2010;Murphy et al, 2010;Tili et al, 2007) have been shown to be involved in the LPS-induced regulation of TNF-a expression. In macrophages, the expression levels of miR-155 are known to be induced by LPS treatment, while those of miR-125b are reduced (Tili et al, 2007).…”
Section: Suppression Of Fascin Expression Results In Alterations Of Mmentioning
confidence: 99%
“…Gram-negative bacterial cell walls contain LPS endotoxins, which are well known to increase miR-146a and miR-155 in RAW264.7 macrophages and miR-146a, miR-132, and miR-155 in THP-1 monocytes in vitro [23, 37]. A previous study of human periodontal disease gingiva found miR-146a increased but miR-155 reduced relative to healthy tissues [38].…”
Section: Discussionmentioning
confidence: 99%